Higher Education as Context for Music Pedagogy Research - Angelo, Elin; Knigge, Jens; Sæther, Morten; Waagen, Wenche (MusPed:Research, 2021)
"This anthology presents music pedagogical research as a field of integrated reflection that transcends institutional and disciplinary barriers. The anthology aims to reinforce thinking, knowledge development and collaboration in the broad landscape of music pedagogical research and education. The authors are associated with performance music education, pre-service and in-service teacher education, specialist music teacher education, and early childhood teacher education. Through 14 chapters, the anthology examines admission tests and assessment guidelines in performing music education, music in interdisciplinary work in teacher education, notions of musicality in early childhood teacher education, entrepreneurship in higher music education, the principle instrument in general music teacher education, evaluation of concert production in music teacher education, multiculturalism across various music teacher educations, pipe organ education for children, dilemmas in Scandinavian choir-leader education, work experiences of female professors in music education, a performing musician's path to becoming a researcher, state funding and the mandate of performance music education, and the discursive terms of music/teacher education at four institutions of higher education. The topics and discussions addressed in these chapters are central across the higher educational programs that qualify students to teach in the various fields of music education."